IMPLEMENTASI PROGRAM PENERBITAN AKTA KELAHIRAN BERBASIS ONLINE PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN TANA TORAJA - Azahrya, Ira; Tahir, Muhammad; Yahya, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to find out what the implementation of online-based birth certificates is like. Using qualitative research methods with collection techniques using observation, interviews and documentation. The data analysis process includes data reduction, data presentation and conclusion drawing. The results of this study use 5 indicators of service quality, namely the first crying (physical evidence) in the form of existing facilities. The second is the dimension of reliability (reliability) which is the ability of service providers to provide services that are correct and reliable. The third dimension of responsiveness (response) is the willingness to help and provide services. The four guarantees (guarantees) can briefly be interpreted as an employee's knowledge and ability to be trusted and trusted. The five empathy (empathy) referred to here is to give sincere attention in serving.